Can an Ice-Cream Based Supplement Help Address Malnutrition in Orthogeriatric Patients?. Issue 4 (2nd October 2021) - Taib, Adnan; Ong, Terence; Mulvaney, Emily; Neale, Chris; Strawther, Nicola; Peters, Christina; Sahota, Arun; Sahota, Opinder
Abstract: Using a Plan-Do-Study-Act (PDSA) methodology, we describe our first cycle of a project using an ice-cream oral nutritional supplement (ONS ice-cream) to address malnutrition in older patients. A Scandishake-based ® (Nutricia) vanilla flavored ice-cream was developed and piloted on a cohort of orthopedic patients over 3 days. All suitable patients were offered 100 g ice-cream portions (240 kcal/per portion). Acceptability and energy intake were our primary outcomes. Over 3 days, the ONS ice-cream was accepted in 77% ( n  = 27, median age, 75 years, IQR 12.5) of the times offered. Among these patients the average energy intake per day including the ONS ice-cream was 1006 kcal, a 41% increase in energy intake compared to an initial nutritional survey among the older orthopedic patients (714 kcal, p  = 0.010). When surveyed 84% ( n  = 16) of patients stated they would have the ONS ice-cream again. An ONS ice-cream intervention to improve energy intake in older adults is feasible.